Utilización de vinagre ácido acético e infusión de oreganon plectranthus amboinicus como prebiótico en el levante de pollos criollos gallus domesticus tipo mejorados - Chiriboga Chuchuca, Carlos Luis (2014)
This investigative work was carried out in the experimental farm "Santa Inés" of the Technical University of Machala, county of El Oro and it was made with the following objectives: 1. to check the productive parameters in the one rises of Creole chickens using acetic acid (vinegar) and oregano infusion like natural prebióticos. 2. to determine the effectiveness of the acetic acid (vinegar) and oregano infusion in the one rises of Creole chickens. 3. to determine the profitability in the one rises of Creole birds with the use of acetic acid (vinegar) and oregano infusion. One worked during everything the one he/she lifts that I last 42 days with 160 Creole chickens "Gallus Domesicus" improved type, they were distributed at random in 16 groups of 10 chickens each one, considering 4 treatments (T1 = vinegar, T2 = vinegar and oregano infusion, T3 = oregano infusion, T4 witness) with 4 repetitions each one. For this work, in the feeding it was used balanced free of antibiotics to determine the effectiveness of the treatments, the data of food consumption and consumption of water were gathered tried daily, it was weighed the chickens weekly until the end of the investigation and the samples of grounds to analyze them in the laboratory they were gathered in half to the beginning and at the end of the investigation. The variables to investigate were: gain of weight, food consumption, nutritious conversion, mortality, production limit and also in the laboratory microbiológico total flora, colimetria, mushrooms and yeasts were analyzed. As conclusions we can say that in the field variables significant results were not obtained with regard to the treatment witness, but in the laboratory the T1,T2 marked differences with regard to the witness, but the T3 mark he/she differs on the T1, T2, T4. Being able to say that the treatment of oregano infusion went effective when reducing the total flora and colimetria.